2005
DOI: 10.4049/jimmunol.174.4.1841
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expanded Myeloid Precursors Function as Regulatory Antigen-Presenting Cells and Promote Tolerance through IL-10-Producing Regulatory T Cells

Abstract: The initiation of graft-vs-host disease (GVHD) after stem cell transplantation is dependent on direct Ag presentation by host APCs, whereas the effect of donor APC populations is unclear. We studied the role of indirect Ag presentation in allogenic T cell responses by adding populations of cytokine-expanded donor APC to hemopoietic grafts that would otherwise induce lethal GVHD. Progenipoietin-1 (a synthetic G-CSF/Flt-3 ligand molecule) and G-CSF expanded myeloid dendritic cells (DC), plasmacytoid DC, and a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 51 publications
5
130
1
Order By: Relevance
“…49 Further, Waller et al 50 recently found an association between the number of pDCs within BM graft and OS, but failed to show any correlation between pDCs in PBSC and outcome or GVHD.…”
Section: Mobilized Pbsc: the Immunological Perspective F Saraceni Et Almentioning
confidence: 99%
“…49 Further, Waller et al 50 recently found an association between the number of pDCs within BM graft and OS, but failed to show any correlation between pDCs in PBSC and outcome or GVHD.…”
Section: Mobilized Pbsc: the Immunological Perspective F Saraceni Et Almentioning
confidence: 99%
“…12,[16][17][18] To study the effect of RelB within recipient APCs, BMCs received 950 cGy (split dose separated by 3 hours on day 0) and were transplanted with 5 ϫ 10 6 bone marrow and 3 ϫ 10 6 purified splenic T cells from Balb/c (allogeneic) or B6 (syngeneic) donors. For donor T reg depletion studies, Balb/c mice were injected intraperitoneally with 500 g anti-CD25 mAb (PC61) or control mAb (rat IgG1 isotype control MAC49) on day Ϫ4 prior to transplantation.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…19 Animals with severe clinical GVHD (scores Ն 6) were killed according to ethical guidelines, and the day of death was deemed to be the following day, as previously described. 12,16,17,20 Statistics Survival curves were plotted using Kaplan-Meier estimates and compared by log-rank analysis. The Mann Whitney U test was used for the statistical analysis of cytokine data and clinical scores.…”
Section: Assessment Of Gvhdmentioning
confidence: 99%
“…Although in the allogeneic setting regulatory T cell (Treg) accumulation triggered by myeloid Gr1 ϩ CD11b ϩ suppressor cells (MSC) reduces acute graft-versus-host disease (GVHD) 1 but instead worsens chronic GVHD, 2 in autoimmune diseases the expansion of Treg is expected to be beneficial. In the experimental model of spontaneous autoimmune diabetes in nonobese diabetic (NOD) mice, we have recently demonstrated 3 that Lin Ϫ Sca1 hi ckit hi Flt3 ϩ CD34 ϩ CD106 ϩ CD127 Ϫ multipotent hematopoietic progenitor cells (HPCs) mobilized to the spleen by a combination of granulocytecolony stimulating factor (G-CSF) and FMS-like tyrosine kinase 3 ligand (Flt3L), have a tolerogenic potential and that their transplantation halts autoimmune diabetes.…”
Section: Introductionmentioning
confidence: 99%